The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2006
DOI: 10.1073/pnas.0601932103
|View full text |Cite|
|
Sign up to set email alerts
|

A live, attenuated recombinant West Nile virus vaccine

Abstract: authors note that Fig. 5 did not include all vaccine study groups. The corrected figure and legend appear below. This error does not affect the conclusions of the article. Confidence intervals for Spearman's rank correlation of log 10 IFN-␥ producing PBMC per million and log10 stimulation index were based on Fisher's transformation. On day 14, the correlation was 0.491 (95% CI, 0.231-0.686); on day 28, the correlation was 0.188 (95% CI: Ϫ0.112 to 0.456).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
119
1
3

Year Published

2007
2007
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 208 publications
(131 citation statements)
references
References 31 publications
(29 reference statements)
5
119
1
3
Order By: Relevance
“…Recent clinical studies have indicated that antigenic chimeric flaviviruses are attenuated and immunogenic in human volunteers and may serve as live attenuated virus vaccines for protection against disease caused by DEN, JE, WN, and TBE viruses [27][28][29][30][31]. These positive results observed in several clinical trials support the further development and study of antigenic chimeric flaviviruses.…”
Section: Discussionmentioning
confidence: 87%
“…Recent clinical studies have indicated that antigenic chimeric flaviviruses are attenuated and immunogenic in human volunteers and may serve as live attenuated virus vaccines for protection against disease caused by DEN, JE, WN, and TBE viruses [27][28][29][30][31]. These positive results observed in several clinical trials support the further development and study of antigenic chimeric flaviviruses.…”
Section: Discussionmentioning
confidence: 87%
“…An effective dose is determined by several parameters, including how efficiently a vaccine virus replicates in infected cells in vivo in a given model. For instance, the live ChimeriVax-WN vaccine was more immunogenic in humans than in mice and monkeys (27,28). Based on recent epidemiological data for WN virus in North America, the WN backbone of RV-WN/TBE should enable efficient (single-cycle) replication in humans, and therefore an appropriate immunizing dose will need to be determined in clinical trials.…”
Section: Discussionmentioning
confidence: 99%
“…Attenuation of YFV-17D has been attributed to mutations in the YFV-17D envelope protein, which may hinder spread of the virus to visceral tissues, and was recently linked to reduced quasispecies diversity (Beck et al, 2014;Hahn et al, 1987;Lee & Lobigs, 2008). Considering that YFV-17D is currently being used in chimeric vaccines to JEV, and for the development of vaccines to WNV and DENV, a better understanding of its attenuation is imperative (Guirakhoo et al, 2006;Guy et al, 2010;Monath et al, , 2006Pugachev et al, 2005).…”
Section: Introductionmentioning
confidence: 99%